Answer:
Joanne’s solution is incorrect
The correct solution in the procedure
Step-by-step explanation:
we have
[tex]x^{2}-10x-11=0[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]x^{2}-10x=11[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex]x^{2}-10x+25=11+25[/tex]
[tex]x^{2}-10x+25=36[/tex]
Rewrite as perfect squares
[tex](x-5)^{2}=36[/tex]
So far Joanne's procedure was correct, then she was wrong to take the square root on both sides.
take square root both sides
[tex](x-5)=(+/-)6[/tex]
[tex]x=5(+/-)6[/tex]
[tex]x1=5(+)6=11[/tex]
[tex]x2=5(-)6=-1[/tex]
The solution is [tex]x=11[/tex] or [tex]x=-1[/tex]